2013
DOI: 10.1002/pssb.201349158
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport through short dsDNA measured with mechanically controlled break junctions: New thiol–gold binding protocol improves conductance

Abstract: It is shown that double‐stranded DNA which is directly coupled to gold via a modified thymidine base exhibits a higher conductance than reported for DNA coupled to metal electrodes using different binding schemes. The measurements of electrical conductance are performed in a mechanically controlled break junction setup in aqueous solution and in high vacuum at room temperature. The current–voltage characteristics obtained in vacuum can be understood if a single molecular energy level determines the transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Furthermore, the conductance appeared to be thermally activated. This resembled semiconductive behavior, which has been previously observed for single DNA molecules trapped in break junctions [49] and self-assembled monolayers of thiolfunctionalized DNA. The temperature-dependence of the conductance suggested hopping as charge transport mechanism along the DNA, as expected for DNA molecules, which are in contact with a substrate.…”
Section: (8 Of 12)supporting
confidence: 81%
“…Furthermore, the conductance appeared to be thermally activated. This resembled semiconductive behavior, which has been previously observed for single DNA molecules trapped in break junctions [49] and self-assembled monolayers of thiolfunctionalized DNA. The temperature-dependence of the conductance suggested hopping as charge transport mechanism along the DNA, as expected for DNA molecules, which are in contact with a substrate.…”
Section: (8 Of 12)supporting
confidence: 81%
“…Finally, DNA molecules with a length of were observed to act as insulators, but below this length conductance could be observed that can be related to the base stacking of the ds-DNA. It has been demonstrated that stacks of CG-pairs act as relatively well conducting links along the DNA, while AT-pairs rather resemble tunneling barriers [ 31 , 32 ]. It is, however, challenging to generate stable conformations of DNA assemblies, which are exceeding the length of a few nanometers, with stacks of GC-pairs, only.…”
Section: Dna Metalizationmentioning
confidence: 99%
“…In the first, proximate electrodes are fabricated and the molecules are located in the gap between them, and measured by a two‐probe transport setup . In the second, a gap is formed by mechanically controllable break‐junction technique or by current heating . In the third approach, one end of the molecule is chemically linked to a metallic substrate, while the other end is attached to a conductive local‐probe tip of either a scanning tunneling microscope (STM) or an atomic force microscope (AFM), allowing two‐probe transport measurements …”
Section: Introductionmentioning
confidence: 99%